Sovereign credit ratings and central banks: Why do analysts pay attention to institutions?. (18th July 2018) - Bodea, Cristina; Hicks, Raymond
Abstract: This paper studies the effect of the governance of modern central banks on the ratings assigned by the credit rating agencies Standard and Poor's and Moody's. Until recently, the rating process was not public. Even still, the factors or precise methodologies used by the agencies remain uncertain and analyst judgment remains important. We argue that, given uncertainty over the future paths of countries, the quality of the central bank governance serves as a useful heuristic for a stable and favorable country trajectory. In particular, the central bank's independence signals that the government is committed to general macroeconomic stability, including debt repayment. Additionally, central bank transparency clarifies who is the principal of the bank and provides information about how the central bank understands the economy and monetary policy. Finally, tensions between the central bank and the government, as reflected by irregular turnover of central bank governors, raise doubts about countries' future prospects. Empirically, we use a variety of models, including mediation analysis, to ensure that the effect we identify stems from the central bank governance itself, as a heuristic for the future paths of countries, and not the central bank's direct contribution to the macroeconomy, as reflected in the available data.